Behavior-Specific Praise in Pre-K–12 Settings: Mapping the 50-Year Knowledge Base. (May 2020) - Ennis, Robin Parks; Royer, David James; Lane, Kathleen Lynne; Dunlap, Kristin Diane
Behavior-specific praise (BSP) is a low-intensity strategy widely used to encourage appropriate behavior. We sought to explore the vast literature base for BSP, which spans 50 years, to better understand for whom and under what conditions BSP has demonstrated effectiveness. We conducted a comprehensive review of school-based intervention studies ( k = 57) involving BSP with school-age students. First, we identified outlets in which these 57 studies (from 52 articles) were featured. Second, we described the 1, 947 total student participants and the educational contexts in which these interventions occurred—the vast majority of students were served in general education and many displayed challenging behaviors (e.g., students with emotional and behavioral disorders). Third, we examined how BSP was implemented and evaluated with the Pre-K–12 population, noting three distinct areas of research: teacher-delivered BSP, student-delivered BSP, and professional learning to increase BSP. Fourth, we examined how BSP was employed as an independent and dependent variable, with more than 96% of studies featuring BSP as an outcome measure. Finally, we investigated the extent to which social validity (33 studies), generalization (11 studies), and maintenance (26 studies) were assessed. We conclude with a discussion of limitations and directions for future inquiry.